2020
DOI: 10.1044/2019_lshss-19-00017
|View full text |Cite
|
Sign up to set email alerts
|

A Hearing Screening Pilot Study With Students With Significant Cognitive Disabilities

Abstract: Purpose Many children with severe intellectual and developmental disabilities are at a higher risk for hearing loss than their peers who are typically developing. Unfortunately, they do not consistently participate in routine school-based hearing screenings. The current study investigated the feasibility of increasing their participation using an otoacoustic emissions protocol and documented results relative to student educational profiles. Method A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This way, the hearing state of the athlete is assessed automatically and without the need of any active participation by the athlete. DPOAE as assessment tool has been validated as well in the general population (Hall & Swanepoel, 2009; Joint Committee on Infant Hearing [JCIH], 2007), as in people with intellectual disability (Nederlandse Vereniging van Artsen voor Verstandelijke Beperking [NVAVG], 2019; Quick et al, 2020). The DPOAE screening either yields a ‘pass’ (hearing level threshold of <30 dBHL) or a ‘no pass’.…”
Section: Methodsmentioning
confidence: 99%
“…This way, the hearing state of the athlete is assessed automatically and without the need of any active participation by the athlete. DPOAE as assessment tool has been validated as well in the general population (Hall & Swanepoel, 2009; Joint Committee on Infant Hearing [JCIH], 2007), as in people with intellectual disability (Nederlandse Vereniging van Artsen voor Verstandelijke Beperking [NVAVG], 2019; Quick et al, 2020). The DPOAE screening either yields a ‘pass’ (hearing level threshold of <30 dBHL) or a ‘no pass’.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the high prevalence level of hearing loss in patients with IDD, studies have also shown a positive correlation between the severity of IDD and hearing loss [9]. Finally, many studies highlight that hearing loss often goes unidentifed and undertreated in patients with IDD, with previously undiagnosed hearing loss ranging from 19% to 58.7% [5,[10][11][12][13]. While hearing loss in patients without IDD can negatively impact multiple spheres of life such as cognition, communication, social contacts, safety, and occurrence of depression, patients with IDD are even more vulnerable to these consequences, making early screening, diagnosis, and treatment vital [10].…”
Section: Prevalence Of Hearing Loss In Patients With Iddmentioning
confidence: 99%